Properties of thermoplastic composite using sesendok and kelempayan sawdust at different filler loading of polypropylene / Noorshashilawati Azura Mohammad … [et al.] - Mohammad, Noorshashilawati Azura; Khairudin, Faerul Hafiz; Kasim, Jamaludin; Mohd Hassan, Nurul Husna (2012)
This study provides mechanical and physical properties of wood plastic composite from Sesendok and Kelempayan. In this study, polypropylene was used due to the high curing temperature and high strength. The effect of different filler loading of 40 mesh Sesendok and Kelempayan sawdust such as 10%, 30%, and 50% were performed. The properties of bending strength, internal bonding (IB), thickness swelling (TS) and water absorption (WA) were evaluated base on ASTM standard. From the study, it showed that filler loading and type of species affected the physical and mechanical properties of wood plastic composite.